"I Know What You're Feeling…": Narrative Observations Reveal Underlying Symptomatology. Issue 1 (2nd January 2023) - Pascual-Leone, Antonio; Yakoub, Donika; Adil, Derya; Soucie, Kendall
Abstract: Psychological symptoms are nested within autobiographical narratives. The narrative emotion process coding system (NEPCS) describes how people tell stories, identifying problematic narratives: Same Old Story, Empty Story, Unstoried Emotion, and Superficial Story. These markers refer to observable narrative features rather than a story's content. Although related to the psychotherapy process, they have not been used to predict symptom distress independently. The current study examined whether the way people recount their stories is qualitatively different depending on the types of mental health symptoms they are suffering. 160 students suffering distress over unresolved personal issues completed clinical symptom inventories of depression, anxiety, and trauma and then completed 15 minutes of expressive writing. Written accounts were reliably coded for problematic narratives using the NEPCS. When a participant's expressive writing sample revealed one or more problematic narrative, it predicted they were suffering more symptoms of anxiety ( d = .70), depression ( d = .44), and trauma ( d = .33); such that they either approached or surpassed clinically relevant cutoffs. Problematic narratives explained 15.2% of symptom reports about anxiety, 9.6% for depression, and 7.8% for trauma. Narratives predicted symptomatology. Same old story and superficial story were the strongest predictors and associated with all dimensions of symptom distress.